Metallofullerene single-molecule magnet Dy2O@C2v(5)-C80 with a strong antiferromagnetic Dy⋯Dy coupling. Issue 51 (7th June 2022) - Velkos, Georgios; Yang, Wei; Yao, Yang-Rong; Sudarkova, Svetlana M.; Liu, Fupin; Avdoshenko, Stanislav M.; Chen, Ning; Popov, Alexey A.
Abstract : Dysprosium-oxide clusterfullerene Dy2 O@ C 2v (5)-C80 is a single-molecule magnet with very strong antiferromagnetic superexchange Dy⋯Dy coupling via the μ2 -O 2− bridge. Abstract : Dysprosium-oxide clusterfullerene Dy2 O@ C 2v (5)-C80 is a single-molecule magnet featuring antiferromagnetic superexchange Dy⋯Dy coupling via the μ2 -O 2− bridge, the strongest of its kind among Dy2 complexes with non-radical bridges.